The efficacy and safety of cadonilimab combined with lenvatinib for first-line treatment of advanced hepatocellular carcinoma (COMPASSION-08): a phase Ib/II single-arm clinical trial - Qiao, Qian; Han, Chun; Ye, Sisi; Li, Juan; Shao, Guoliang; Bai, Yuxian; Xu, Aibing; Sun, Meili; Wang, Wei; Wu, Jian; Huang, Ming; Song, Lijie; et al. (Frontiers in Immunology, 2023)
This multicenter, open-label, phase Ib/II study aimed to assess the efficacy and safety of cadonilimab, a humanized, tetravalent, bispecific antibody plus lenvatinib in first-line treatment of aHCC.Methods: Patients with histologically confirmed aHCC were included to receive either 6 mg/kg cadonilimab every two weeks plus lenvatinib (cohort A) or 15mg/kg cadonilimab every three weeks plus lenvatinib (cohort B). The primary endpoint was objective response rate (ORR) by RECIST v1.1, while the secondary endpoint were safety, progression-free disease (PFS), overall survival (OS), disease control rate (DCR), duration of response (DoR) and time to response (TTR).Results: A total of 59 patients were enrolled (31 in cohort A and 28 in cohort B). The median follow-up time was 21.22 months as of the data cutoff date (February 27, 2023). The ORR in cohort A was 35.5% (95% CI: 19.2, 54.6) and 35.7% (95% CI: 18.6, 55.9) in cohort B, and the median DoR was 13.6 months (95% CI: 4.14, NE) and 13.67 months (95%CI: 3.52, NE), respectively. The median PFS was 8.6 months (95%CI: 5.2, 15.2) and 9.8 months (95%CI: 6.9, 15.2), respectively. Grade ≥ 3 treatment-related adverse events (TRAEs) were reported in 66.1% of patients, with serious TRAEs occurring in 39.0% of cases. Decreased platelet count (47.5%), proteinuria (45.8%), hypertension (44.1%), and white blood cell count decreased (44.1%) were the most common TRAEs.This novel combination therapy showed promising efficacy and manageable toxicity that could provide an option in first-line setting of aHCC.